Inter- and intra-individual variability in the kinematics of the back squat - Kristiansen, M.; Rasmussen, G. H. F.; Sloth, M. E.; Voigt, M. (Human Movement Science, 2019)
The purpose of this study was to explore the level of inter- and intra-individual variability in the kinematic profiles of the back squat movement among skilled weightlifters. Ten competitive weightlifters volunteered for participation in this study. Barbell velocity (VBarbell) and angular velocity of the ankle ( Ankle), knee ( Knee) and hip joint ( Hip) were obtained by kinematic recording of six trials at 90% of 1RM in the back squat. Inter-individual variability was assessed by analysing inter-individual differences in the velocity curves through the statistical parametric mapping method. Intra-individual variability was assessed through a correlation analysis between the barbell velocity curves of each trial for each participant. Partial least squares regression analysis, was performed to relate changes in intra-individual variability to movement and anthropometric characteristics. Significant inter- and intra-individual differences were identified in VBarbell, Ankle, Knee, and Hip (p = 0.05). Having a short trunk and thigh, and a long shin in combination with greater anterior-posterior displacement of the barbell and slower velocities during the acceleration phase increased intra-individual movement consistency over movement variability. The results of the present study clearly demonstrate that skilled weightlifters display both significant inter- and intra-individual variability in the successful execution of the back squat.